2022
DOI: 10.3389/fneur.2021.795076
|View full text |Cite
|
Sign up to set email alerts
|

Associated Factors and Prognostic Implications of Non-convulsive Status Epilepticus in Ischemic Stroke Patients With Impaired Consciousness

Abstract: Background and Purpose: Non-convulsive status epilepticus (NCSE) is common in patients with disorders of consciousness and can cause secondary brain injury. Our study aimed to explore the determinants and prognostic significance of NCSE in stroke patients with impaired consciousness.Method: Consecutive ischemic stroke patients with impaired consciousness who were admitted to a neuro intensive care unit were enrolled for this study. Univariate and multivariable logistic regression were used to identify factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 44 publications
1
13
0
1
Order By: Relevance
“…Four of the NCSE patients subsequently died in the course of their hospital stay without showing any clinical improvement following the initiation of appropriate antiseizure medication despite the abolishment of the seizure activity [ 20 ]. Cerebral injury also accounts for the 62% mortality rate we found in patients exhibiting any type of seizure postoperatively and replicates findings by other researchers who showed that poor outcomes were primarily seen in seizure patients who concomitantly presented with new brain injury [ 3 , 8 , 18 ]. Even if there is no visible structural damage detected in the CCT images, subtle neuronal insults may occur in the context of CPB [ 21 , 22 , 23 ], which cause encephalopathy and might also induce epileptic activity in susceptible patients [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Four of the NCSE patients subsequently died in the course of their hospital stay without showing any clinical improvement following the initiation of appropriate antiseizure medication despite the abolishment of the seizure activity [ 20 ]. Cerebral injury also accounts for the 62% mortality rate we found in patients exhibiting any type of seizure postoperatively and replicates findings by other researchers who showed that poor outcomes were primarily seen in seizure patients who concomitantly presented with new brain injury [ 3 , 8 , 18 ]. Even if there is no visible structural damage detected in the CCT images, subtle neuronal insults may occur in the context of CPB [ 21 , 22 , 23 ], which cause encephalopathy and might also induce epileptic activity in susceptible patients [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…Due to its subtle symptoms, NCSE can easily be missed or misidentified and can only be verified via an EEG, resulting in frequent undertreatment [ 5 ]. The overall rate of occurrence of NCSE in critically ill patients lies somewhere between 8% and 40% whereupon NCSE can contribute to secondary brain injury [ 7 , 8 ]. Status epilepticus in general is a risk factor for poor outcomes after focal or global brain ischemia, which is not uncommon in heart surgery [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The articles included 1967 patients (9.8%) with early seizures and 10 605 patients (52.7%) with late seizures after stroke; 7538 seizures (37.5%) were not classified as early or late. PSS were diagnosed according to clinical or medical chart data in 59 studies and using the ICD-10 codes in 12 studies (including 15 033 patients [74.8%]). Patients with PSS had a significantly higher history of ischemic heart disease (OR, 1.3; 95% CI, 1.1-1.6), prior cerebrovascular disease (OR, 1.3; 95% CI, 1.0-1.6), atrial fibrillation (OR, 1.2; 95% CI, 1.1-1.4), and the presence of hemorrhagic transformation (OR, 2.2; 95% CI, 1.6-3.0) than patients without PSS (eTable 3 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
“…Der non-konvulsive Status epilepticus, eine Komplikation nach Schlaganfall, wird ohne Langzeit-EEG nicht erkannt und kann zur schlechteren Prognose beitragen. Deshalb wird insbesondere bei bewusstseinsgetrübten Patienten nach Schlaganfall ein Langzeit-Video-EEG-Monitoring empfohlen [26].…”
Section: Schlaganfallunclassified